Teachers’ attitudes towards reflective teaching: evidences in a professional development program (pdp) (2008)
Reflective teaching is a paradigm that dominates teacher education around the world and most professional development programs include it as a way to improve teachers’ practice. As a teacher educator I am aware of the importance reflective teaching (RT) has on teachers’ professional development. This article reports a research experience with two in-service teachers of English enrolled in a professional development program at a public university in Bogotá who initiated a reflective teaching process through the development of reflective thinking skills. Data were gathered through interviews, observation, videotaping, questionnaires and a diary. Findings showed some teachers’ attitudes towards RT, the possible factors that might have stimulated and lessenedreflection, and some of the changes observed in their teaching practice. Key words: Reflective teaching, reflective thinking skills, professional development program, teaching practice La enseñanza reflexiva es un paradigma que domina la educación de docentes en el mundo y la mayoría de programas de desarrollo profesional (PDP) la incluyen como una manera de mejorar la práctica de los docentes. Como docente educadora, soy consciente de su importancia en el desarrollo profesional. Este artículo describe una experiencia investigativa con dos profesores de inglés participantes en un PDP en una universidad pública en Bogotá, quienes iniciaron un proceso de reflexión sobre su práctica docente mediante el desarrollo de habilidades de pensamiento reflexivo. Los datos se recolectaron mediante entrevistas, observación, video grabación, cuestionarios y un diario. Los resultados mostraron algunas actitudes de los docentes hacia la enseñanza reflexiva, los posibles factores que pudieron estimular e inhibir la reflexión y algunos cambios en su práctica docente. Palabras claves: Enseñanza reflexiva, habilidades de pensamiento reflexivo, programa de desarrollo profesional, práctica docente